2017
DOI: 10.5101/nbe.v9i2.p112-123
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Rapid Crystallization of L-Alanine Using Monomode Microwaves, Indium Tin Oxide and Metal-Assisted and Microwave-Accelerated Evaporative Crystallization

Abstract: The use of indium tin oxide (ITO) and focused monomode microwave heating for the ultra-rapid crystallization of L-alanine (a model amino acid) is reported. Commercially available ITO dots (< 5 mm) attached to blank poly(methyl)methacrylate (PMMA, 5 cm in diameter with 21-well silicon isolators: referred to as the iCrystal plates) were found to withstand prolonged microwave heating during crystallization experiments. Crystallization of L-alanine was performed at room temperature (a control experiment), with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…It is reported that the most dominant crystal growth direction is also the most energetically favorable [43]. The orientation effect could be affected by the solution composition, polarity, and charge density of substrates, and the intermolecular interaction energy between the solute and surface [45][46][47]. At 0.14 g/g H 2 O, crystals present a dendritic morphology (Figure 4b).…”
Section: Gah Concentrationmentioning
confidence: 95%
“…It is reported that the most dominant crystal growth direction is also the most energetically favorable [43]. The orientation effect could be affected by the solution composition, polarity, and charge density of substrates, and the intermolecular interaction energy between the solute and surface [45][46][47]. At 0.14 g/g H 2 O, crystals present a dendritic morphology (Figure 4b).…”
Section: Gah Concentrationmentioning
confidence: 95%